Development of laser speckle blood flowmeter for evaluating the physiological function of skin. (23rd August 2019) - Nagashima, Yoshinao; Ohsugi, Yuko; Hiraishi, Makiko; Niki, Yoshifumi; Fuji, Akira; Majima, Masataka; Okamoto, Takashi
Abstract: Objective : We developed and demonstrated laser speckle flowgraphy (LSFG) for two-dimensional (2D) skin blood flow (SBF) measurements to facilitate the noninvasive comparisons of SBF between individuals. Approach : By using morphing technology with a face mesh to compare SBF spatial distributions among individuals, we examined the practicability of SBF measurement with LSFG. Main results : (1) The uniformity of SBF measurement was demonstrated by examinations at different distances and angles for healthy subjects. (2) Mean blur rate (MBR)—a blood flow index of LSFG—exhibited significant correlation with the thermal diffusion method (TDM)—an established blood flow measurement method—suggesting that MBR is an effective index of SBF. (3) Blowout time, the half-width duration/duration of one cardiac cycle, exhibited significant negative correlation with age and positive correlation with stratum corneum hydration. Significance : These results suggest that LSFG is useful for evaluating SBF-related skin properties, and it has significant potential in medicine and cosmetology.